2021
DOI: 10.3390/land10030306
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Impacts of Habitat Changes on the Population Density of Eurasian Skylark (Alauda arvensis) Based on Its Landscape Preferences

Abstract: The dramatic decline of the abundance of farmland bird species can be related to the level of land-use intensity or the land-cover heterogeneity of rural landscapes. Our study area in central Europe (Hungary) included 3049 skylark observation points and their 600 m buffer zones. We used a very detailed map (20 × 20 m minimum mapping unit), the Hungarian Ecosystem Basemap, as a land-cover dataset for the calculation of three landscape indices: mean patch size (MPS), mean fractal dimension (MFRACT), and Shannon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…Landscape configuration (area, perimeter, and shape of patches; number of patches; largest patch index) and composition (area of open areas) variables significantly influenced the bird assemblages in the studied forests, in agreement with Calamari and Zaccagnini [9] and Carrara et al [2]. They are also in agreement with other studies, for example [7,66]; our results reject the habitat size hypothesis proposed by Fahrig [67] because it was found that not only the composition (OTA variable) but also the configuration (AREA, PERIM, SHAPE, FNP, ONP, OLPI, OCONNECT, TE, and ED) of the landscape influenced the assemblage of birds. As observed by Klingbeil and Willig [14], migratory birds (e.g., E. albiceps and T. leucopyga) showed a very weak association with landscape variables, which could be associated with the fact that these are long-distance migrants capable of adapting to many different environments [51,68].…”
Section: Discussionsupporting
confidence: 91%
“…Landscape configuration (area, perimeter, and shape of patches; number of patches; largest patch index) and composition (area of open areas) variables significantly influenced the bird assemblages in the studied forests, in agreement with Calamari and Zaccagnini [9] and Carrara et al [2]. They are also in agreement with other studies, for example [7,66]; our results reject the habitat size hypothesis proposed by Fahrig [67] because it was found that not only the composition (OTA variable) but also the configuration (AREA, PERIM, SHAPE, FNP, ONP, OLPI, OCONNECT, TE, and ED) of the landscape influenced the assemblage of birds. As observed by Klingbeil and Willig [14], migratory birds (e.g., E. albiceps and T. leucopyga) showed a very weak association with landscape variables, which could be associated with the fact that these are long-distance migrants capable of adapting to many different environments [51,68].…”
Section: Discussionsupporting
confidence: 91%
“…However, when comparing fractal distributions to uniform ones, a fractal form will not necessarily mean higher density. Urban areas with similar density measurements can have very different fractal dimensions, as shown in Figure 3 in [81] Consequently, fractal dimension cannot be used as a proxy for density; rather, it can supplement density metrics to distinguish between urban and rural areas in large-scale urban regions [82][83][84][85][86][87].…”
Section: How Does Fractal Dimension Indicate History and Institutiona...mentioning
confidence: 99%
“…With the acceleration of LULC changes that occurred with urban expansion, economic growth, and explicitly/implicitly increasing human needs, the monitoring of LULC changes became a key tool that could be used in work associated with environmental protection and sustainable development. LULC maps are often used as base data in environmental studies conducted in fields such as agriculture (Bezdan et al, 2019), hydrology (Tobak et al, 2019), ecology (Csikós & Szilassi, 2021), urbanization (Steurer & Bayr, 2020), and change detection (Szilassi, 2017). LULC mapping is a widely discussed topic in the field of remote sensing because remote sensing can provide tools, and reliable and extensive data with a high temporal and spatial resolution for LULC mapping (Townshend et al, 1991).…”
Section: Introductionmentioning
confidence: 99%